2022
DOI: 10.3390/metabo12010082
|View full text |Cite
|
Sign up to set email alerts
|

Hao1 Is Not a Pathogenic Factor for Ectopic Ossifications but Functions to Regulate the TCA Cycle In Vivo

Abstract: Ossification of the posterior longitudinal ligament (OPLL), a disease characterized by the ectopic ossification of a spinal ligament, promotes neurological disorders associated with spinal canal stenosis. While blocking ectopic ossification is mandatory to prevent OPLL development and progression, the mechanisms underlying the condition remain unknown. Here we show that expression of hydroxyacid oxidase 1 (Hao1), a gene identified in a previous genome-wide association study (GWAS) as an OPLL-associated candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…HAO1 is a peroxisomal enzyme that can regulate the tricarboxylic acid cycle. in oxidative stress [24,25]. EGR4 is involved in the regulation of learning, synaptic plasticity and memory dysfunction, and is implicated in the pathogenesis of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…HAO1 is a peroxisomal enzyme that can regulate the tricarboxylic acid cycle. in oxidative stress [24,25]. EGR4 is involved in the regulation of learning, synaptic plasticity and memory dysfunction, and is implicated in the pathogenesis of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Mainly expressed in the liver and pancreas, HAO1 is mostly active against the dicarbon substrate glycolate [28]. Additionally, recent studies have shown that HAO1 regulates TCA circulation [29], and targeted therapy of the HAO1 gene is expected to solve hyperoxaluria. HMGCLL1 is a highly homologous gene with HMGCL reported in the Genome Database in 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxyacid oxidase 1 (Hao1) was inactivated in mice, in the frame of its potential association with spinal canal stenosis, but no ectopic ossification was noticed [118].…”
Section: Other Peroxisomal Matrix Proteinsmentioning
confidence: 99%